Continuous salt stress-induced long non-coding RNAs and DNA methylation patterns in soybean roots - Rui Chen (BMC Genomics, 2019)
Abstract Background Environmental stimuli can activate a series of physiological and biochemical responses in plants accompanied by extensive transcriptional reprogramming. Long non-coding RNAs (lncRNAs), as versatile regulators, control gene expression in multiple ways and participate in the adaptation to biotic and abiotic stresses. Results In this study, soybean seedlings were continuously cultured for 15 days with high salinity solutions started from seed germination. Strand-specific whole transcriptome sequencing and stringent bioinformatic analysis led to the identification of 3030 long intergenic non-coding RNAs (lincRNAs) and 275 natural antisense transcripts (lncNATs) in soybean roots. In contrast to mRNAs, newly identified lncRNAs exhibited less exons, similar AU content to UTRs, even distribution across the genome and low evolutionary conservation. Remarkably, more than 75% of discovered lncRNAs that were activated or up-regulated by continuous salt stress mainly targeted proteins with binding and catalytic activities. Furthermore, two DNA methylation maps with single-base resolution were generated by using reduced representation bisulfite sequencing, offering a genome-wide perspective and important clues for epigenetic regulation of stress-associated lncRNAs and protein-coding genes. Conclusions Taken together, our findings systematically demonstrated the characteristics of continuous salt stress-induced lncRNAs and extended the knowledge of corresponding methylation profiling, providing valuable evidence for a better understanding of how plants cope with long-term salt stress circumstances.